Effect of family history of atrial fibrillation on recurrence after atrial fibrillation ablation: A report from the Chinese Atrial Fibrillation Registry Study. (10th February 2021) - Wu, Zhuanzhuan; Jiang, Chao; Li, Jingye; Du, Jing; Bai, Yu; Guo, Xueyuan; Wang, Wei; Li, Songnan; Jiang, Chenxi; Liu, Nian; Tang, Ribo; Bai, Rong; et al.
Abstract: Background: To evaluate the impact of family history of atrial fibrillation (FAF) on postablation atrial tachyarrhythmia (AT) recurrence. Methods: All the 8198 patients undergoing initial AF ablation registered in the Chinese Atrial Fibrillation Registry study were analyzed. FAF was defined as having first‐degree relatives diagnosed as AF at age 65 years or younger, and before the time the case in this study was diagnosed. Cox proportional hazards models were used to evaluate the impact of FAF on postablation AT recurrence. Age, sex, body mass index, AF type, history of congestive heart failure, hypertension, diabetes mellitus, prior stroke/transient ischemic attack/systemic embolism, vascular diseases, use of contact force‐sensing catheter, and completion of high school were adjusted. The definition of AT recurrence was any documented AF, atrial flutter, or AT lasting more than or equal to 30 s after 3 months blanking period. Results: After a mean follow‐up of 26.2 ± 19.6 months, 318 out of the 645 patients (49.3%) with FAF and 3339 out of the 7553 patients (44.2%) without FAF experienced AT recurrence, corresponding to annual recurrence rates of 22.8% and 20.2%, respectively. Patients with FAF had a significant higher risk of AT recurrence (adjusted hazard ratio 1.129, 95% confidence interval 1.005–1.267) in multivariable analysis. Moreover, FAF had a significant higher impact on AT recurrence in the subgroup of patients diagnosed with AF at age 50 years or younger ( p for interaction = .036). Conclusion: FAF is a risk factor for postablation AT recurrence. This is especially true in those with AF diagnosed at 50 years or younger.